Cultivating Leadership Skills within the Organization Among the Management of Karang Taruna in Helvetia Village - Siahaan, Maya; Brina, Melda (Jurnal Pengabdian Masyarakat Bestari, 2024)
The implementation of the Community Service activity aims to foster leadership spirit within the Karang Taruna organization in Helvetia Village. This objective aligns with the current and contemporary developments of the times. Additionally, the activity seeks to motivate Karang Taruna members to develop leadership qualities in this millennial era. The execution approach involves utilizing counseling techniques through projectors, seminars, discussion forums, and Q&A sessions. The expected outcome of this activity is not only to provide additional knowledge but also to broaden the insights of Karang Taruna members, which can be specifically applied to hone organizational skills. Moreover, it is anticipated that this activity will assist and enhance their leadership with the latest and millennial-appropriate approaches.